A preliminary stury on ectoparasite composition of wild birds in Ba Be national park - Hung, Nguyen Manh; Hien, Hoang Van (Academia Journal of Biology, 2012)
The knowledge and published paper the ectoparasites of wild birds in Vietnam are very little. In fact, there are some specialized references that provided biological characteristics, ecology and the distribution of this group in several parts of Vietnam, but the conditions as well as research purposes set out, only focus of interest on livestocks and animals, which live near the human i.e. mice (Rodentia). This paper reported that 12 individuals of the total 45 birds captured in Ba Be national park infected with ectoparasites. The infectious intensity of ectoparasites on those birds was from 1 to 38 samples. Two ectoparasite species were determined as Myrsidea ochracei and Brueelia alophoixi, five suggested ectoparasites species are undetermined.